The Role of Motion Design in the Formation of Dynamic Brand Style (Laisvalaikio tyrimai, 2020)
Research background. Today, in order for the company to be easily recognized and stay inthe trend, there is not enough ordinary advertising. It should be a progressive design work.Advertising is an important element in the development of a market economy, it should carry thecontinuation of the dynamic corporate identity. Motion design in advertising provides identification.Effectively using the visual memory of consumers and using stable forms of "one among strangers",creates a positive emotional attitude. Also, the use of motion elements in advertising emphasizes thecompany's trend.Research goal – systematization of approaches regarding the definition of the concept ofmotion design. Research objectives: to reveal the role and main characteristics of motion design inthe formation of a dynamic corporate identity of a company; to explore the main aspects of motiondesign in the formation of a dynamic corporate identity of the company.Methods. Abstracting, comparative analysis and synthesis, systematic and structureddynamic styles of Ukrainian and international companies, which made it possible to highlight thesignificant role of motion design in increasing brand awareness of the company.Results. The role of motion design in the formation of a dynamic corporate identity isrevealed, the basic requirements are identified, and the trends in the advertising of enterprises realizedwith the help of motion design in the continuation of a dynamic corporate identity are analyzed.Conclusions. The development of companies translates into a qualitative change in the liferealities of a person in the context of globalization and a dynamic change of news. Among the hugeflow of information, advertising is a necessary tool for influencing the consumer to consolidate thedynamic image of the company. Well-designed motion design allows you to combine different groupsof products under a single brand, which enhances the advertising impact on the consumer.Keywords: motion design, promotion, brand, color, dynamic corporate identity